2018
DOI: 10.1103/physreva.97.022309
|View full text |Cite
|
Sign up to set email alerts
|

Multiqubit subradiant states in N -port waveguide devices: ε-and-μ-near-zero hubs and nonreciprocal circulators

Abstract: Quantum emitters interacting through a waveguide setup has been proposed as a promising platform for basic research on light-matter interactions and quantum information processing. Here, we propose to augment waveguide setups with the use of multiport devices. Specifically, we demonstrate theoretically the possibility of exciting N-qubit subradiant, maximally entangled, states with the use of suitably designed N-port devices. Our general methodology is then applied based on two different devices: an epsilon-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Researchers have been interested in enhancing the strength and extending the range of radiative interactions, with applications in energy sciences and quantum technologies. While lots of progress has been made in the past decades, we observed that there has a been a trade-off in many methods studied in the literature [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The trade-off occurs between the strength and the range: interactions with a long range are often weak in strength while strong interactions are very short range.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Researchers have been interested in enhancing the strength and extending the range of radiative interactions, with applications in energy sciences and quantum technologies. While lots of progress has been made in the past decades, we observed that there has a been a trade-off in many methods studied in the literature [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The trade-off occurs between the strength and the range: interactions with a long range are often weak in strength while strong interactions are very short range.…”
Section: Introductionmentioning
confidence: 95%
“…A general strategy to enhance radiative interaction strength and range is to place transitions in engineered photonic environments, where the optical modes can be drastically different from those in vacuum. This strategy was used in many interesting works that enhance the range [4,[7][8][9][10][11]13] or the strength [20,21,28,29]. For example, zero-index materials can extend the range of coupling [7][8][9][10][11] to Fℓ 0 , where the enhancement factor F can be a few hundreds.…”
Section: Introductionmentioning
confidence: 99%
“…where H.c. denotes the Hermetian conjugate and we have assumed a frame rotating at the frequency of the emitters, ω 0 . The coupling parameters can then be written as [38]…”
Section: Appendix B: Coupling Between the Emittersmentioning
confidence: 99%
“…From a theoretical standpoint, collective effects give rise to new phenomena that enhance our understanding of basic light-matter interaction processes. Some examples include superradiance [1,2], subradiance [3,4], collective Lamb shift [5,6], modification of temporal correlations [7,8], strengthening of the coupling to an optical mode [9], and the interplay between strong coupling and quenching [10]. From a more practical perspective, the emission properties of ensembles of quantum emitters are relevant for the design of nonclassical light sources, which are of general interest for quantum technologies [11][12][13].…”
Section: Introductionmentioning
confidence: 99%